Professional burnout of medical workers in wartime conditions: historical analysis, current research, and author’s definition - Rusanov, Volodymyr (Psychosomatic Medicine and General Practice, 2024)
Relevance Professional burnout among medical workers is an urgent problem in the modern healthcare system, especially in Ukraine, where medical professionals operate under conditions of military conflict. Constant stress, high demands on work quality, limited resources, and extreme conditions significantly increase the risk of emotional and physical exhaustion. Burnout affects not only the well-being of the medical staff but also the quality of medical care provided to the population. The increasing cases of burnout among medical workers during wartime underscore the necessity for an in-depth study of this phenomenon and the development of effective strategies for its prevention and mitigation. Aim The aim of this article is to conduct a historical analysis of the formation of the concept of "professional burnout" among medical workers, provide a critical review of current research and gaps in the study of this phenomenon, and develop an author’s definition of professional burnout in the context of medical workers operating in wartime conditions. Materials and Methods To achieve the research goal, a qualitative and quantitative content analysis of scientific literature dedicated to professional burnout among medical workers in wartime conditions was conducted. Literature searches were performed using international databases such as PubMed, CrossRef, Web of Science, and Google Scholar, covering the last 15 years (2008–2023). Based on the obtained data, an author’s definition of professional burnout for medical workers in wartime conditions was developed. Conclusions The conducted analysis demonstrated that professional burnout is a complex, multidimensional phenomenon that manifests particularly acutely among medical workers during wartime. The historical development of the burnout concept reflects a shift from an individual to a systemic approach, emphasizing organizational and systemic factors. An author’s definition of professional burnout among medical workers in wartime conditions has been proposed, which takes into account the specific stress factors characteristic of this group. It has been determined that effective strategies for the prevention and overcoming of burnout should be based on a comprehensive approach, combining individual and organizational interventions. The necessity for further research in this field is urgent, especially considering the cultural and contextual peculiarities of medical workers’ activities in conditions of military conflict.